Analysis of the Implementation of PSAP No.13 Concerning Presentation of Financial Statments for Regional Public Service Bodies at Cigombong Health Center Bogor - Triwidatin, Yuppy; Hidayatullah, Rizki (LPPM STIE PPI, 2024)
Introduction/Main Objectives: To analyze the presentation of the financial statements of regional public service agencies (BLUD) at the Cigombong Community Health Center, Bogor Regency, based on the implementation ofi PSAP No. 13. Background Problems: There are standards that are not met in the preparation of financial reports, especially the presentation of information that is very useful in making decisions that refer to government regulations (pp.71/2010). Novelty: Retesting the same analysis conducted by previous researchers with different locations. Research Methods: The comparative qualitative method is a method used to determine the comparison between PSAP No. 13 and the financial reports. Findings/Results: The research confirm that the presentation of financial statements of the Cigombong Community The BLUD Health Center in Bogor Regency is not in accordance with PSAP Number 13; however, there are some that are appropriate, especially reports ofi changes in excess budget balances, cash flow reports, reports ofi changes in capital and notes on financial reports. Conclusion: Are not fully in accordance with PSAP Number 13 are budget realization reports, balance sheets and operational reports it is recommended for Cigombong Health Center, especially in the presentation of financial reports, to continue to be consistent in the effort to present reliable and trustworthy financial reports by referring to PSAP Number 13 in accordance with the provisions.